ANALISIS PERCEPATAN DEGRADASI POME (Palm Oil Mill Effluent) MENGGUNAKAN NITROGEN DAN PHOSPATE DENGAN INTERVAL WAKTU 10 DAN 20 HARI - Jefira Dea Savitri; Arie Ikhawan Saputra; Jubaidi, Jubaidi (Jurnal Sanitasi Profesional Indonesia, 2024)
Indonesia is one of the palm oil producing countries, The waste produced by palm oil is Palm Oil Mill Effluent (POME). POME is the residual waste water from palm oil waste in the form of a brownish viscous liquid containing water (95-96%), oil (0.6-0.7) and 4-5% total solids. Each production of 1 ton of TBS be formed. about 0.6 to 1 m3 POME. The purpose of this study was to measure the acceleration of POME biodegradation after the administration of various doses of Phosphate and Sampling technique using "times series Nitrogen by measuring the COD value against the length of incubation time. Sampling technique using "times series’. There was a decrease in the accelerated biodegradation of COD content at the highest dose ratio at N5:P3 with a value of 33.60%:19.20% after the addition of various nitrogen and phosphate dosage variants to the blank for 10 days. There was a decrease in the accelerated biodegradation of COD content at the highest dose ratio in N2:P4 with a value of 33.60%: 28.80% after the addition of various nitrogen and phosphate doses to the blank for 20 days. For other researchers, they can add various dose comparisons to continue the research that has been done previously to make it even better.